Intervention for Recoarctation in the Single Ventricle Reconstruction Trial: Incidence, Risk, and Outcomes - Hill, Kevin D.; Rhodes, John F.; Aiyagari, Ranjit; Baker, G. Hamilton; Bergersen, Lisa; Chai, Paul J.; Fleming, Gregory A.; Fudge, J. Curt; Gillespie, Matthew J.; Gray, Robert G.; Hirsch, Russel; Lee, Kyong-Jin; et al. (Circulation (New York, N.Y.), 2013)
BACKGROUND—Recoarctation after the Norwood procedure increases risk for mortality. The Single Ventricle Reconstruction (SVR) trial randomized subjects with a single right ventricle undergoing a Norwood procedure to a modified Blalock-Taussig shunt or a right ventricle–pulmonary artery shunt. We sought to determine the incidence of recoarctation, risk factors, and outcomes in the SVR trial. METHODS AND RESULTS—Recoarctation was defined by intervention, either catheter based or surgical. Univariate analysis and multivariable Cox proportional hazard models were performed with adjustment for center. Of the 549 SVR subjects, 97 (18%) underwent 131 interventions (92 balloon aortoplasty, 39 surgical) for recoarctation at a median age of 4.9 months (range, 1.1–10.5 months). Intervention typically occurred at pre–stage II catheterization (n=71, 54%) or at stage II surgery (n=38, 29%). In multivariable analysis, recoarctation was associated with the shunt type in place at the end of the Norwood procedure (hazard ratio, 2.0 for right ventricle–pulmonary artery shunt versus modified Blalock-Taussig shunt; P=0.02), and Norwood discharge peak echo-Doppler arch gradient (hazard ratio, 1.07 per 1 mm Hg; P<0.01). Subjects with recoarctation demonstrated comorbidities at pre–stage II evaluation, including higher pulmonary arterial pressures (15.4±3.0 versus 14.5±3.5 mm Hg; P=0.05), higher pulmonary vascular resistance (2.6±1.6 versus 2.0±1.0 Wood units·m; P=0.04), and increased echocardiographic volumes (end-diastolic volume, 126±39 versus 112±33 mL/BSA, where BSA is body surface area; P=0.02). There was no difference in 12-month postrandomization transplantation-free survival between those with and without recoarctation (P=0.14). CONCLUSIONS—Recoarctation is common after Norwood and contributes to pre–stage II comorbidities. Although with intervention there is no associated increase in 1-year transplantation/mortality, further evaluation is warranted to evaluate the effects of associated morbidities. CLINICAL TRIAL REGISTRATION—URLhttp://www.clinicaltrials.gov. Unique identifierNCT00115934.